To Promote or Hire? How Racial Processes and Organizational Characteristics Affect Internal Promotions in NCAA Division I College Basketball Coaching. (4th September 2019) - Seebruck, Ryan; Savage, Scott V
Abstract: We use data from 2008–2013 on the universe of internal promotion opportunities in the labor market of NCAA Division I men's college basketball coaching to examine how race and racial homophily affect the likelihood of internal promotion. We run probit regression analyses from the individual and organizational perspective, offering a robust test of six hypotheses. In line with the relational inequality perspective, we find that the racial match of assistants and head coaches explains discrepancies in internal promotion, with homogeneous white pairings seeing significantly increased odds compared to other racial combinations. In addition, our findings reveal that colleges and universities are more likely to promote internally as the racial composition of the staff more closely matches the race of the outgoing head coach, thereby underscoring how racial processes inform the micro-level interactions that shape organizational behavior.